Self-Diffusion Studies in Polystyrene Nuclear Grade Resin - Lokhande, R.S.; Ingale, M.N. (Asian Journal of Chemistry, 2010)
The self-diffusion studies of Cr3+ and Fe3+ ions in a gel type polystyrene sulphonic acid resin (nuclear grade) was carried out. All the plots obtained for self-diffusion of Cr3+ and Fe3+ ions in nuclear grade cation exchanger Indion-223 show the linear relationship and the tendency of passing through origin.